ASUHAN KEPERAWATAN BERBASIS EVIDENCE PADA PASIEN DIABETES MELLITUS TIPE 2 DENGAN DIABETIC FOOT ULCER DERAJAT WAGNER GRADE 2: STUDY KASUS - Isrofah, Isrofah; Yulistiani, Mustiah; Listiyaningrum, Nurul Hidayati (SINERGI : Jurnal Riset Ilmiah, 2026)
Diabetic foot ulcer (DFU) is a common chronic complication of type 2 diabetes mellitus associated with peripheral neuropathy, poor glycemic control, infection, and increased risk of amputation. This case report aims to describe evidence-based nursing care for a patient with type 2 diabetes mellitus presenting with a Wagner grade 2 diabetic foot ulcer using the SDKI, SIKI, and SLKI frameworks. A 58-year-old male presented with a plantar ulcer on the right foot for three weeks, accompanied by pain, seropurulent exudate, erythema, and elevated blood glucose levels (random blood glucose 286 mg/dL; HbA1c 9.4%). Wound assessment revealed a 3.2 × 2.4 cm ulcer with a depth of 0.8 cm, partial slough, moderate exudate, and no gangrene, consistent with Wagner grade 2 classification. Priority nursing diagnoses included impaired tissue integrity, acute pain, risk of infection, and unstable blood glucose levels. Nursing interventions focused on aseptic wound care, infection monitoring, offloading, pain management, patient education, and glycemic control. After five days of care, clinical improvements were observed, including reduced pain, decreased exudate, improved wound condition, and better glycemic trends. These findings are consistent with current evidence emphasizing comprehensive DFU management, including wound care, pressure reduction, infection control, and optimal glycemic management to enhance healing and prevent complications